Assessing the quality of trust features on website content of top hospitals for medical tourism consumers - Moslehifar, Mohammad Ali; Noor Aireen Ibrahim; Shanti C. Sandaran (Penerbit Universiti Kebangsaan Malaysia, 2016)
Searching for health information online is one of the most common activities on the internet; therefore, continuous evaluation of the quality of information provided in these health websites is indeed important. In the context of medical tourism, trust is a particularly important feature of quality information. This becomes even more significant online as customers have to trust the information on the website, since tourism products are characterized by high intangibility before consumption. Although trust plays an essential role among health care providers and individuals who are seeking health care information; there is a question about what happens to trust once health information goes online. One possible reason is that people who seek information from web sites figure a sense of trust in the web sites they visited. As such, this research will assess the quality of trust features of the top 10 medical tourism website. Findings of the research showed variation in the level of quality of trust features on the web site with Gleneagles Hospital fulfilling the highest score of trust features, while the Asklepios Klinik Barmbek website scored the least. The findings of this study have significant implications for web site developers and medical tourism consumers.